SELEKSI GALUR DARI POPULASI F4 KEDELAI YANG TAHAN TERHADAP PENYAKIT MOSAIK (Soybean mosaic virus) DAN BERDAYA HASIL TINGGI - Wuye Ria Andayanie; Praptiningsih Gamawati Adinurani (Universitas Lampung, 2014)
Soybean lines selection of F4 population resistant to soybean mosaic disease (Soybean mosaic virus) with high yield. The soybean breeding program is usually not purposedly done for resistance to Soybean mosaic virus (SMV) but rather for crop yields. The experiment was aimed to obtain soybean lines of F4 population resistant to soybean mosaic disease with high yield. F2-F4 plants that have been inoculated with the T isolate of SMV one week after planting were selected by the pedigree in the screen house. The result indicated eight F4 populations (Wilis x L. Temanggung; Wilis x L. Jombang; Wilis x Pangrango; Wilis x PI 200485; Gepak Kuning x L. Jombang; Gepak Kuning x L. Temanggung; Gepak Kuning x Malabar; Gepak Kuning x PI 200485) produced medium seed size (from 9.84-10.26 g 100/seeds). Gepak Kuning x Mlg 3288 showed more resistant than Gepak Kuning x PI 200485. The seed produced by Gepak Kuning x PI 200485 was 1.97 ton/ha. There were no F4 populations that had higher yield and bigger seed size than Gepak Kuning x PI 200485 even though they were moderately resistant to SMV. Therefore, these lines of Gepak Kuning x Mlg 3288 and Gepak Kuning x PI 200485 might provide exellent sources to develop a new variety that resistant to SMV and of high yield.